STRATEGIES FOR PREVENTING AND HANDLING BULLYING IN PRIMARY SCHOOLS - Eka Ramiati; Indana Zulfa; Mufidah Yusroh (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2025)
Primary education encompasses not only academic achievement but also the cultivation of students' character. A significant challenge in this context is the rising incidence of bullying within school settings. This study aims to examine the role of teachers in addressing bullying among second-grade students at MI Salafiyah Asy-Syafi’iyah Temuguruh. This research employs a qualitative method. The findings reveal that teachers assume roles as educators, mentors, and advisors by implementing moral development strategies. In responding to both physical and verbal bullying, teachers adopt persuasive, empathetic, and humanistic approaches. Nevertheless, the effectiveness of these efforts is hindered by the absence of clear school policies and limited parental involvement. The study affirms the pivotal role of teachers as key agents in fostering an anti-bullying culture within primary education environments.